In vitro rumen fermentation characteristics of ammoniated stover of Samurai 2 sorghum fertilized with different level of Urea. (March 2019) - Anggraeni, A S; Herdian, H; Sofyan, A; Istiqomah, L; Anwar, M; Karimy, M F; Afany, M R; Ekaningrum, M
Abstract: The limitation stock of forages in dry season cause serious problem for ruminant productivity. Various efforts have been made to obtain an alternative feed. Samurai 2 has a high productivity, immune to leaf rust disease and midrange rot and suitable for animal feed. However, sorghum stover is a poor-quality fodder, low in protein and digestibility. It is needing to be processing to increase nutritive value by providing a source of protein and or non-protein and certain minerals through ammoniation. The effect of ammoniation treatments on a sorghum stover on in vitro feed fermentation and gas production on ruminal fluid was the main objective of this study. P12 treatment gave highest gas production than other treatment. Total gas production 48 hours, gas production from soluble fraction ( a ) and insoluble fraction (b) also total fraction ( a+b ) of the sorghum stover was significantly affected by treatments (P<0.05). Volatile Fatty acid (VFA), in vitro degradability, NH3, and biomass microbial rumen indicated no significant difference among treatments. In this study sorghum stover using basic fertilizer 90 kg/ha with ammoniation treatment has the best degradability on rumen fermentation characteristics in vitro of sorghum stover.